Bovine tuberculosis in African buffalo (Syncerus caffer): Progression of pathology during infection. - Hilary Ann Lakin; Hannah Tavalire; Kaori Sakamoto; Peter Buss; Michele Miller; Sarah A Budischak; Kristina Raum; Vanessa O Ezenwa; Brianna Beechler; Anna Jolles (Public Library of Science (PLoS), 2022)
Background Bovine tuberculosis (BTB) is a zoonotic disease of global importance endemic in African buffalo (Syncerus caffer) in sub-Saharan Africa. Zoonotic tuberculosis is a disease of global importance, accounting for over 12,000 deaths annually. Cattle affected with BTB have been proposed as a model for the study of human tuberculosis, more closely resembling the localization and progression of lesions in controlled studies than murine models. If disease in African buffalo progresses similarly to experimentally infected cattle, they may serve as a model, both for human tuberculosis and cattle BTB, in a natural environment. Methodology/principal findings We utilized a herd of African buffalo that were captured, fitted with radio collars, and tested for BTB twice annually during a 4-year-cohort study. At the end of the project, BTB positive buffalo were culled, and necropsies performed. Here we describe the pathologic progression of BTB over time in African buffalo, utilizing gross and histological methods. We found that BTB in buffalo follows a pattern of infection like that seen in experimental studies of cattle. BTB localizes to the lymph nodes of the respiratory tract first, beginning with the retropharyngeal and tracheobronchial lymph nodes, gradually increasing in lymph nodes affected over time. At 36 months, rate of spread to additional lymph nodes sharply increases. The lung lesions follow a similar pattern, progressing slowly, then accelerating their progression at 36 months post infection. Lastly, a genetic marker that correlated to risk of M. bovis infection in previous studies was marginally associated with BTB progression. Buffalo with at least one risk allele at this locus tended to progress faster, with more lung necrosis. Conclusions/significance The progression of disease in the African buffalo mirrors the progression found in experimental cattle models, offering insight into BTB and the interaction with its host in the context of naturally varying environments, host, and pathogen populations.